STUDI TENTANG SULAMAN TANGAN PADA PELAMINAN TRADISIONAL NARAS DI KECAMATAN PARIAMAN UTARA KOTA PARIAMAN - Wahyuni, Sri; Idrus, Yenni; Novrita, Sri Zulfia (Journal of Home Economics and Tourism, 2015)
Hand embroidery on the traditional wedding Naras Pariaman is a skill that is acquired from generation to generation, so entrepreneurs are still using the old motifs. As the development of science and technology entrepreneurs aisle switch embroider using embroidery machine. The data used are primary data obtained from business leaders and craftsmen, secondary data is data obtained from the following documents photographs. Informants in this study is the wedding business owners and craftsmen (maker motif) embroidered. The technique of collecting data through observation, interviews and documentation. The data analysis technique since before entering the field, while in the field, and after completion in the field, by performing data reduction, data presentation, and conclusion. The results of this study found that hand embroidery design motifs used on the altar Naras naturalist and geometric motifs. Types of hand embroidery used namely lekapan technique that attaches embroidery threads contained in the curtain wall, lelansir, waves, tongues, langik-langik batirai, Banta sieve, Ankin-Ankin, and dalamak. Embroidery attach beads / sequins are also present in the curtain wall, lelansir, waves, tongues, langik-langik batirai, Banta sieve, Ankin-Ankin, and dalamak. Gold thread embroidery using glass found on the veil, langik-langik batirai, Banta sieve and dalamak. Application of hand embroidery found in parts of the traditional wedding curtain walls, lelansir, waves, tongues, langik-langik batirai, Banta sieve, Ankin-Ankin, and dalamak. Kata kunci: sulaman tangan, pelaminan, Naras